The Influences of Using Quizizz in Student’s English Learning Outcomes - Abdul Jalil Jum’uatullaila; Buhari; Syahrir L; Sam Hermansyah (Program Studi Pendidikan Bahasa Inggris, Universitas Pendidikan Muhammadiyah Sorong, 2025)
This research aims to examine the influence of using Quizizz, a game-based digital learning platform, on students' English learning outcomes at SMA Muhammadiyah Pangsid. This study employs a quantitative approach with a quasi-experimental design using pre-test and post-test assessments to measure the impact. The sample consisted of 20 students selected through simple random sampling. Data collection techniques included reading tests, questionnaires, observations, and statistical analysis using paired sample t-test. The results show a significant improvement in students’ English proficiency after using Quizizz, indicated by the average score increase from 26.55 (pre-test) to 38.75 (posttest). Questionnaire analysis revealed that students responded positively to the use of Quizizz, with high levels of motivation, engagement, and enjoyment. Observational data also demonstrated increased classroom participation and collaboration. These findings suggest that Quizizz not only enhances academic performance but also fosters a more interactive and engaging learning environment.